Satisfaction Towards An Enrichment Programmes: Halal Action For Young Scientists Camp - Nur Fazidah Asmuje; Rosita Zainal; Amnah Zanariah Abd Razak; Ahmad Hakimi Shafie; Nurul Elma Sabri; Anis Liyana Nabihah Jamil (Universiti Teknologi Mara (UiTM), 2024)
Indexed by MYCITE